Digital Intelligence for Technical Students: Use of Online Mind Map in Enhancing Design Thinking - Abd. Karim, Rafidah; Mustapha, Ramlee; Aliasak, Mohd Hasrol Haffiz; Raslee, Nor Nadia; Ghani, Nurul Farhani Che (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
In a world dominated by digitalization, digital intelligence is critical. Digital intelligence is required for education, employment, and active participation in the community. Digitalization has transformed our way of thinking, feeling, and living, and its rapid evolution has made change, which was once the exception, the norm. As a result, change management has emerged as a fundamental skill for people in the 21st century. But far more important than this is the development of digital intelligence, which, to be developed, necessarily requires disruptive education. An online mind map is a visual aid that is becoming extremely prevalent in today's classrooms. Given the importance of empirical research and evaluation, it is perhaps surprising that so little effort has been directed toward the application of online mind mapping among technical students to enhance design thinking. This study aims to examine Malaysian technical students’ perspectives with regards to the use of an online mind map to enhance design thinking. 372 technical students from selected public higher institutions were involved in this study. A quantitative method using an online survey was conducted for the students. The results from questionnaire items and open-ended items were analyzed using descriptive and inferential statistics and thematic analysis. The findings from the study revealed that the technical students agreed that the online mind map helped them enhance their design thinking. The study makes important contributions on how the tool can develop design thinking in technical terms to address IR4.0 needs and produce balanced graduates who are globally competitive. Finally, this study contributes a new framework for technical students’ design thinking.